Prevalence and outcomes of atrial fibrillation in older people living in care homes in Wales: a routine data linkage study 2003–2018. (3rd October 2022) - Ritchie, L A; Harrison, S L; Penson, P E; Akbari, A; Torabi, F; Hollinghurst, J; Harris, D; Oke, O B; Akpan, A; Halcox, J P; Rodgers, S E; Lip, G Y H; et al.
Abstract: Background: Older care home residents are a high-risk group of people with atrial fibrillation (AF) who are under-represented in clinical trials. Improved understanding of AF epidemiology and management in this population is paramount for health and social care organisations to strategically plan services. Purpose: To determine the trends in AF prevalence and compare adverse health outcomes in older care home residents aged ≥65 years with AF compared to those without AF. Methods: Retrospective cohort study of people entering a care home between 2003–2018 using nationwide, population-scale anonymised health and administrative data, provisioned from the Secure Anonymised Information Linkage (1 January 2000–31st December 2018). Direct standardisation was used to calculate AF prevalence by year of care entry (2010–2018). Cox regression analyses were used to estimate the risk of adverse health outcomes. Results: Between 2003 and 2018, 86, 602 people aged ≥65 years became new residents in care homes in Wales. Residents with AF (n=14, 493) had a significantly higher risk (adjusted hazard ratio [aHR], 95% confidence interval [CI]) of cardiovascular (aHR 1.27 [1.17 to 1.37], p<0.001) and all-cause mortality (aHR 1.14 [1.11 to 1.17], p<0.001), Figure 1. The risk (sub-distribution hazard ratio [sHR], 95% CI) of ischaemic stroke (adjusted sHR 1.55 [1.36 to 1.76], p<0.001) and cardiovascular hospitalisation (adjusted sHR 1.28 [1.22 to 1.34], p<0.001) was also higher in residents with AF, even when mortality was considered a competing event, Figure 1. There was no significant change in age- and sex-standardised prevalence of AF between 2010 and 2018, 16.79% (95% CI 15.85 to 17.94) and 17.02% (95% CI 16.05 to 17.98), respectively (absolute change 2010–2018: 0.06% [95% CI: −1.38 to 1.50], p=0.93), Figure 2. Conclusions: This study demonstrates unique data on the epidemiology of AF and associated outcomes in older care home residents. Whilst the prevalence of AF remained stable between 2010–2018, residents with AF had significantly higher risk of adverse health events. Treatment of AF in accordance with guidelines is critical in this population to optimise management and reduce adverse health outcomes. Funding Acknowledgement: Type of funding sources: None.